2021
DOI: 10.3390/medsci9010011
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge, Attitudes, and Practice towards COVID-19 Pandemic in Saudi Arabia: A Web-Based Cross-Sectional Survey

Abstract: (1) Background: COVID-19 has become a worldwide public health problem. No previous study has investigated factors associated with COVID-19 knowledge, attitude, and practice (KAP) after completely lifting the curfew in all Saudi Arabia regions and cities. Therefore, adequate knowledge, a positive attitude, and correct control of COVID-19 are essential to eradicate the disease. Hence, this study aims to assess factors associated with KAP of COVID-19; (2) Methods: This cross-sectional web-based survey was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
26
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 42 publications
20
26
3
Order By: Relevance
“…The apparently docile nature of COVID-19 related information recirculation in Saudi Arabian social media platforms is a positive indicator that the general population are aware of the necessary sources, such as the Ministry of Health in Saudi Arabia for getting their information. 36,37 However, consistent with the findings of other studies regarding judging the validity of information on social media platforms, the Saudi Arabian general population are more likely to judge the validity of information based on their own experience, and deem it beneficial for the public to share COVID-19 related information sans evidence. 10,[16][17][18][19][20][21] Thus, it can be posited that Saudi Arabian general population's perception of COVID-19 related information circulating on social media platforms is of a neutral disposition.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The apparently docile nature of COVID-19 related information recirculation in Saudi Arabian social media platforms is a positive indicator that the general population are aware of the necessary sources, such as the Ministry of Health in Saudi Arabia for getting their information. 36,37 However, consistent with the findings of other studies regarding judging the validity of information on social media platforms, the Saudi Arabian general population are more likely to judge the validity of information based on their own experience, and deem it beneficial for the public to share COVID-19 related information sans evidence. 10,[16][17][18][19][20][21] Thus, it can be posited that Saudi Arabian general population's perception of COVID-19 related information circulating on social media platforms is of a neutral disposition.…”
Section: Discussionsupporting
confidence: 67%
“…However, this is not consistent with the findings of previous studies conducted for the Saudi Arabian population, where the Northern Region was seen to be most susceptible. 36 This inconsistency might be not taken into consideration as the number of Northern Region participants in the previously mentioned study is about 1.5% of the total number of participants from other regions; this is the main limitation and weakness of Alnasser et al's 2020 study 36 and it might affect the reliability of the study regarding participants' regional distribution. The current study is suggestive that regardless of the location, there is at least a 1 in 2 chances that the resident might have recirculated information on social media platforms.…”
Section: Discussionmentioning
confidence: 94%
“…Binary logistic regression analysis about the practices showed that age, high level of attitude about COVID-19, and higher education were associated with better practices toward COVID-19. This study is consistent with the study by Alnasser et al, showing that the highest level of good practices regarding COVID-19 pandemic was of those aged 35–50, and of those with a bachelor's degree ( 32 ). The correlations between attitudes and practices had been well-established in various studies ( 16 , 33 ).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Indonesian females were also reported avoiding prayers, physical gatherings and take preventive measures at worship places during the COVID-19 pandemic than males [24]. In general, our results are also consistent with recent studies conducted in Saudi Arabia which reported that younger and women have higher optimistic attitudes towards the COVID-19 pandemic than men [13,14,[25][26][27]. These results can be attributed to the increased usage of the social media channels by younger, females, job seekers as well as housewives, which can improve the Islamic knowledge and attitudes regarding the disease, compared to their counterparts.…”
Section: Discussionsupporting
confidence: 91%